Intranasal Vaccination With Recombinant Antigen-FLIPr Fusion Protein Alone Induces Long-Lasting Systemic Antibody Responses and Broad T Cell Responses - Hsieh, Ming-Shu; Hsu, Chia-Wei; Tu, Ling-Ling; Chai, Kit Man; Yu, Li-Lu; Wu, Chiao-Chieh; Chen, Mei-Yu; Chiang, Chen-Yi; Liu, Shih-Jen; Liao, Ching-Len; Chen, Hsin-Wei (Frontiers in Immunology, 2021)
A simple formulation is urgently needed for mucosal vaccine development. We employed formyl peptide receptor-like 1 inhibitory protein (FLIPr), an FcγR antagonist secreted by Staphylococcus aureus, as a vector to target ovalbumin (OVA) to dendritic cells (DCs) via intranasal administration. Our results demonstrate that intranasal administration of recombinant OVA-FLIPr fusion protein (rOVA-FLIPr) alone efficiently delivers OVA to DCs in nasal lymphoid tissue. Subsequently, OVA-specific IgG and IgA antibodies in the circulatory system and IgA antibodies in mucosal tissue were detected. Importantly, activation of OVA-specific CD4+ and CD8+ T cells and induction of a broad-spectrum cytokine secretion profile were detected after intranasal administration of rOVA-FLIPr alone in immunocompetent C57BL/6 mice. Furthermore, we employed immunodeficient AG129 mice as a Zika virus infection model and demonstrated that intranasal administration of recombinant Zika virus envelope protein domain III-FLIPr fusion protein induced protective immune responses against the Zika virus. These results suggest that antigen-FLIPr fusion protein alone via intranasal administration can be applied to mucosal vaccine development.